Efeito do uso do laser de baixa potência associado ao óleo ozonizado no manejo da sensibilidade pós-clareamento dental – Estudo clínico, randomizado e duplo-cego - Cardoso, Poliana Maria de Faveri (2024)
Tooth whitening is a procedure widely prescribed in cosmetic dentistry because it is an effective and minimally invasive technique, despite the adverse effect of tooth sensitivity, a clinical condition that is difficult to manage. Objective: To evaluate the effect of treatment with ozonated oil associated with low-level laser in the treatment of tooth sensitivity and the degree of tooth whitening. Methodology: A clinical trial with a split-mouth design was conducted. The sample consisted of 30 volunteers randomized into 2 experimental groups (n=30) according to the desensitization protocol. Control (NPFS): Application of potassium nitrate for 10 minutes; (OGN): apply ozonated sunflower oil for 2 minutes with a rubber bowl at low speed. Subsequently, both arches were cleared with 35% hydrogen peroxide for 45 minutes. After the whitening protocol, a low-level laser was applied at infrared wavelength (808nm), 1 J/cm² in the cervical area of the dental element and 1 J/cm² in the region corresponding to the root apex region in both groups. Sensitivity data were analyzed using Friedman's repeated measures ANOVA test, followed by the Durbin-Conover post hoc test (p < 0.05) in the intra-group analysis and the Wilcoxon test (p < 0.05) in the intergroup analysis. The Wilcoxon test (p < 0.05) was used for the degree of whitening for intra-group analysis, and the Mann-Whitney test (p < 0.05) was used for intergroup evaluation , using the JAMOVI software, version 1.2.24. Results: There was no statistically significant difference in the intergroup analysis for the degree of whitening and sensitivity. Conclusion: The use of an association between ozonated oil and low-level laser promoted whitening and desensitizing effects similar to the association between potassium nitrate and low-level laser in the control group in post-tooth whitening sensitivity.